JAMINAN SOSIAL DALAM PANDANGAN IBNU HAZM DAN RELEVANSINYA DENGAN PENGEMBANGAN JAMINAN SOSIAL DI INDONESIA - Atik Wartini (Hunafa: Jurnal Studia Islamika, 2014)
This research is library research that discusses the thought of Ibn Hazm. This research focuses on the study of the methodology of ijtihad of Ibn Hazm. One of the themes of ijtihad of Ibn Hazm  can still, up to the present, be considered is his concept on social assurance.  Ibn Hazm is the follower of the School of Ẓairiyyah who emphasizes more on text of the reality and in some matters rejects qiyas. Therefore, his thought on social assurance  is of importance to study. This research studies the method of ijtihād of Ibn Hazm, his istidlāl and the influence of the School of Zhairiyyah on his ijtihad as well as his istinbāṭ  or  ijtihād on social assurance  for the haves not. Ibn Hazm possesses liberal interpretation to  social assurance. Therefore, his thought on social assurance is of importance to study, particularly when related to the development of the contemporary Islamic Law and to the BPJS that currently grows   in Indonesia.Kata Kunci : Ẓahiriiyah, Ibnu Hazm, Ijtihad, BPJS.